Pengaruh Kompensasi dan Motivasi terhadap Kinerja Karyawan pada CV Arum Sari - Pipit Kurnia; Faldy Herdian (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study aims to analyze how compensation and motivation affect employee performance. The research was conducted at a cracker factory company, CV Arum Sari. The research method used is a qualitative method using a descriptive approach, this research uses data collection techniques by distributing questionnaires/surveys, interviews, documentation and field surveys. The results showed that the compensation system at CV Arum Sari was not sufficient to motivate employees to achieve optimal performance, this is stated in the research results which obtained a value of 39 with a percentage of 39% which fell into the less/low category. Then employee motivation in achieving work goals in the level of employee satisfaction with work motivation is not sufficient, this is stated in the research results which obtained a value of 38 with a percentage of 38% which falls into the less/low category. The performance of CV Arum Sari employees in achieving production targets is satisfactory. Although there are still some problems related to product quality.